A Practical Approach to the Management of Cancer Patients During the Novel Coronavirus Disease 2019 (COVID‐19) Pandemic: An International Collaborative Group - Al‐Shamsi, Humaid O.; Alhazzani, Waleed; Alhuraiji, Ahmad; Coomes, Eric A.; Chemaly, Roy F.; Almuhanna, Meshari; Wolff, Robert A.; Ibrahim, Nuhad K.; Chua, Melvin L.K.; Hotte, Sebastien J.; Meyers, Brandon M.; Elfiki, Tarek; et al. (The oncologist (Dayton, Ohio), 2020)
The outbreak of coronavirus disease 2019 (COVID‐19) has rapidly spread globally since being identified as a public health emergency of major international concern and has now been declared a pandemic by the World Health Organization (WHO). In December 2019, an outbreak of atypical pneumonia, known as COVID‐19, was identified in Wuhan, China. The newly identified zoonotic coronavirus, severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), is characterized by rapid human‐to‐human transmission. Many cancer patients frequently visit the hospital for treatment and disease surveillance. They may be immunocompromised due to the underlying malignancy or anticancer therapy and are at higher risk of developing infections. Several factors increase the risk of infection, and cancer patients commonly have multiple risk factors. Cancer patients appear to have an estimated twofold increased risk of contracting SARS‐CoV‐2 than the general population. With the WHO declaring the novel coronavirus outbreak a pandemic, there is an urgent need to address the impact of such a pandemic on cancer patients. This include changes to resource allocation, clinical care, and the consent process during a pandemic. Currently and due to limited data, there are no international guidelines to address the management of cancer patients in any infectious pandemic. In this review, the potential challenges associated with managing cancer patients during the COVID‐19 infection pandemic will be addressed, with suggestions of some practical approaches. Implications for Practice The main management strategies for treating cancer patients during the COVID‐19 epidemic include clear communication and education about hand hygiene, infection control measures, high‐risk exposure, and the signs and symptoms of COVID‐19. Consideration of risk and benefit for active intervention in the cancer population must be individualized. Postponing elective surgery or adjuvant chemotherapy for cancer patients with low risk of progression should be considered on a case‐by‐case basis. Minimizing outpatient visits can help to mitigate exposure and possible further transmission. Telemedicine may be used to support patients to minimize number of visits and risk of exposure. More research is needed to better understand SARS‐CoV‐2 virology and epidemiology. Cancer patients have an increased risk of contracting COVID‐19. This article addresses the challenges associated with managing cancer patients during the COVID‐19 infection pandemic and suggests some practical approaches.